EFEK MEDIASI KEPUASAN KERJA PADA PENGARUH IKLIM ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN KEUANGAN RSUD DR HARJONO S KABUPATEN PONOROGO - Safitrin, Hadiyana Ayu; Suddin, Alwi; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This research aims to analyses (1) significance effect motivation on organizational commitment; (2) significance effect job satisfaction on organizational commitment; (3) significance effect motivation on employee performance (4) significance effect job satisfaction on employee performance; (5) significance effect organizational commitment on employee performance; (6) effect motivation on employee performance mediated organizational commitment (7) effect job satisfaction on employee performance mediated organizational commitment. This study is sensus research, using location in State Treasury Service Office/KPPN Solo Raya, using sample of 109 employees. Data collecting with questionnaire technique through validity and reliability test. To test hypothesis using path analysis. The result shows that (1) motivation have a significance effect on organizational commitment; (2) job satisfaction have a significance effect on organizational commitment; (3) motivation have a significance effect on employee performance; (4) job satisfaction have a significance effect on employee performance; (5) organizational commitment have a significance effect on employee performance; (6) effect of motivation on employee performance mediated organizational commitment (7) effect of job satisfaction on employee performance mediated organizational commitment.